Sungai dan Identitas Melayu di Sumatera Timur pada Abad XX - Edi Sumarno; Nina Karina; Junita Setiana Ginting; Handoko Handoko (Indonesian Historical Studies, 2018)
In the 20th century, the transformation of identity into Malay in East Sumatra occurred in a pattern similar to that in other regions. This transformation of identity was closely related to the river as a means of transportation at that time. Through rivers, the rural communities carried commodities to be traded at the downstream, where Malay population dominantly lived there. This pattern then formed the upstream communities such as Karo, Toba, Simalungun and Mandailing to settle downstream and become Malays. However, in the mid-20th, the Malay identity began to be abandoned due to a bloody event. This incident made the residents who grew as Malays use their clan again.